mHealth Incentivized Adherence Plus Patient Navigation (MIAPP): protocol for a pilot randomized controlled trial to improve linkage and retention on buprenorphine for hospitalized patients with methamphetamine use and opioid use disorder - Elenore P. Bhatraju; Devin N. Kennedy; Alexander J. Gojic; Matthew Iles-Shih; Joseph O. Merrill; Jeffrey H. Samet; Kevin A. Hallgren; Judith I. Tsui (Addiction Science & Clinical Practice)
Abstract Background Initiation of buprenorphine for treatment of opioid use disorder (OUD) in acute care settings improves access and outcomes, however patients who use methamphetamine are less likely to link to ongoing treatment. We describe the intervention and design from a pilot randomized controlled trial of an intervention to increase linkage to and retention in outpatient buprenorphine services for patients with OUD and methamphetamine use who initiate buprenorphine in the hospital. Methods The study is a two-arm pilot randomized controlled trial (N = 40) comparing the mHealth Incentivized Adherence Plus Patient Navigation (MIAPP) intervention to treatment as usual. Development of the MIAPP intervention was guided by the information-motivation-behavioral skills model and combines financial rewards via mobile health-based adherence monitoring with the “human touch” of a patient navigator. Participants receive financial incentives for submitting videos of themselves taking buprenorphine via smartphone. The Patient Navigator reviews videos and provides treatment adherence coaching, care coordination and motivational enhancement. The intervention is introduced prior to hospital discharge and is offered for 30 days. The primary outcome is linkage to outpatient buprenorphine care within 30 days of hospital discharge. Secondary outcomes include retention on buprenorphine 90 days post discharge, hospital readmissions, and past 30-day methamphetamine use. Discussion Interventions are needed to increase linkage and retention to outpatient buprenorphine among hospitalized patients with OUD, especially for people who co-use methamphetamine. We will examine the MIAPP intervention to improve buprenorphine adherence and linkage to outpatient treatment in a pilot randomized controlled trial which will provide valuable insights about research approaches for hospitalized patients with substance use disorder. Trial registration number: NCT06027814. Date of Initial Release: 08/30/2023. Protocol Version: 03/21/2024.